Factors Affecting Academic Stress among Santri at the Ruhul Islam Anak Bangsa (RIAB) Islamic boarding school in Aceh Besar - Hasni Rauzana; Syarifah Rauzatul Jannah; Elly Wardani (University of Muhammadiyah Malang, 2021)
Introduction: Academic stress is an individual condition that arises because of the many pressures or academic demands that exceed their capacity to feel burdensome. Objectives: This study aimed to determine the factors that influence the level of academic stress among Santri at the Ruhul Islam Anak Bangsa (RIAB) Islamic boarding school in Aceh Besar. Methods This study used an analytic survey with a cross-sectional approach. This study's population were students of Madrasah Aliyah who were in class II at the Ruhul Islam Anak Bangsa Islamic boarding school, 246 students. The sampling technique used a total sampling technique. Analyze data using statistical tests: Chi-square test and multiple logistic regressions. Results: The results indicate that self-efficacy is associated with academic stress levels (p-value 0.040), hardiness is related to academic stress levels (p-value 0.039), achievement motivation has no relationship with academic stress levels (p-value 0.262), and optimism is related to academic stress levels (p-value 0.043). Conclusions: This study concluded that hardiness is the most dominant factor related to academic stress among Santri at the Ruhul Islam Anak Bangsa (RIAB) Islamic boarding school in Aceh Besar (OR: 0.778).